Psycho-Social-Spiritual Well-Being and Grief among Bereaved Adults: A Correlational Study - Andre Novan Andika; Susana Prapunoto (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Psychological, social, and spiritual dimensions have been recognized as influential factors in the bereavement process, studies integrating these components into a unified model of Psycho-Social-Spiritual Well-Being remain limited, particularly within the Indonesian cultural context. This study aimed to examine the relationship between Psycho-Social-Spiritual Well-Being and bereavement responses among adults who experienced the loss of significant others. A quantitative correlational design was employed involving 204 adults in the Ex-Residency of Semarang. Data were collected using the Adult Attitude to Grief Scale (AAG) and the National Institutes of Health–Healing Experience in All Life Stressors (NIH-HEALS). Because grief data were not normally distributed, Spearman’s rho correlation analysis was conducted. The results revealed a significant negative correlation between Psycho-Social-Spiritual Well-Being and bereavement responses r = –.236; p = .001. The majority of participants were categorized as moderate in Psycho-Social-Spiritual Well-Being (70.6%) and bereavement responses (66.2%). These findings indicate that Psycho-Social-Spiritual Well-Being functions as a protective factor in bereavement adjustment. Implications highlight the importance of developing counseling interventions integrating meaning-centered approaches, social support enhancement, and spiritual dimensions to strengthen adaptive coping among bereaved individuals. Keywords: adult adaptation, bereavement, grief, psycho-social-spiritual well-being, spiritual coping